2016
DOI: 10.1017/s0022149x16000602
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Trichinella infections in domestic dogs from Slovakia

Abstract: Trichinellosis is constantly present in the sylvatic cycle in Slovakia, with several sporadic human outbreaks registered since the 1960s. The largest outbreak of trichinellosis occurred in 1998 and was related to the consumption of dog meat that had been added to smoked pork sausages. The aim of this study was to estimate the seroprevalence of Trichinella infection in domestic dogs in various regions of Slovakia. Out of 439 dogs tested, 56 (12.8%) were classified as a seropositive based on the enzyme-linked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…were also recorded in dogs in Slovakia. In total, 12.8% of 439 tested animals were seropositive in the study of Miterpáková et al (2017) . Similar research by Thi et al (2013) in Vietnam revealed seropositivity to Trichinella in 4% of 125 dogs and none of 98 cats.…”
Section: Discussionmentioning
confidence: 99%
“…were also recorded in dogs in Slovakia. In total, 12.8% of 439 tested animals were seropositive in the study of Miterpáková et al (2017) . Similar research by Thi et al (2013) in Vietnam revealed seropositivity to Trichinella in 4% of 125 dogs and none of 98 cats.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the domestic cycle the immune response during Trichinella infection has been widely studied in pigs, under controlled conditions with a known infection dose and species of Trichinella [ 14 , 30 , 36 , 37 , 38 , 39 ], the immunoprevalence of anti- Trichinella antibodies has been also examined in many animals species connected to the sylvatic cycle [ 13 , 24 , 26 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] as the main reservoir of Trichinella nematodes in the environment. Infections in wildlife occur in a natural way—the dose of infection, the timing, and whether they occur once or repeatedly remain unknown.…”
Section: Introductionmentioning
confidence: 99%